Study Experimental on Strength Characteristics of Alkali-Activated Pofa to Soil Stabilization as Subgrade - Toyeb Muhammad; Hakam Abdul; Fauzan; Andriani (Civil and Environmental Engineering)
The subgrade’s good performance is required to support the upper layers. Excessive subgrade deformation causes a degradation in pavement performance. Traditionally, cement is used to improve it, but it’s environmentally unfriendly. Recently, modern methods have been needed to diminish cement use. This study aims to promote Alkali activator POFA (AAP) as a soil mixture binder for the subgrade layer. The subgrade behaviour was assessed by plate load and CBR test on soil, soil-POFA, and soil-AAP mixtures, as well as with SEM morphology observation. The soil is clayey sand with poor gradation. Applying a 2.0 KN load to soil and soil-POFA mixtures obtained decreased deformation in settlements from 3.77 to 3.21 mm. Meanwhile, the soil-AAP mixture exhibited a lower settlement of 0.86 mm only with applied a 5.0 KN load and has bearing capacity with maximum load of 45 kN. Furthermore, a significant increase in the CBR value from 4.4% to 54.0%. The soil-AAP stabilization can improve the mechanism characteristic of the soil becoming denser and reduce deformation. Incorporation of the POFA and alkali activator into soil mixtures leads to the reaction of aluminosilicate synthesis type C-S-H gel. Hence, the AAP is feasible for promoting modern stabilization.